2002
DOI: 10.1046/j.1444-1586.2002.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual faculties in patients with Alzheimer's disease regress to the level of a 4–5‐year‐old child

Abstract: Background:  The present study investigated when children acquire the cognitive abilities and daily living skills that are lost in Alzheimer's disease. Methods:  Among a total of 1046 students in kindergarten and elementary schools affiliated with Gunma University, Japan, five female and five male students in each grade were selected at random and examined by the mini‐mental state examination (MMSE) and physical self‐maintenance scale (PSMS). For comparison, a total of 135 outpatients with Alzheimer's disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
19
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 23 publications
7
19
0
3
Order By: Relevance
“…It should be also noted that the disorganization of these higher order thinking abilities, which are related to fluid intelligence, was found to be present before the appearance of clinically detectable dementia in the participants in the sample of old-old adults. This result seems to be in line with findings indicating that a large proportion of healthy old-old adults shows memory decline which may represent the early stages of a potentially more severe cognitive impairment (Goldman et al, 2001;Shoji et al, 2002;Schmitt et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It should be also noted that the disorganization of these higher order thinking abilities, which are related to fluid intelligence, was found to be present before the appearance of clinically detectable dementia in the participants in the sample of old-old adults. This result seems to be in line with findings indicating that a large proportion of healthy old-old adults shows memory decline which may represent the early stages of a potentially more severe cognitive impairment (Goldman et al, 2001;Shoji et al, 2002;Schmitt et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, researchers have observed the general relationship between aging and development as findings in gerontological research have indicated that the collapse of intelligence in dementia patients causes retrogression to childhood and/or appears to reverse Piaget's developmental stages (de Ajuriaguerra & Tissot, 1968;Rubial-Álvarez, de Sola, Machado, Sintas, Böhm, Sánchez-Benavides, Langohr, Muñiz, & Peña-Casanova, 2013;Shoji, Fukushima, Wakayana, Shizuka-Ikeda, Ikeda, Kawakami, Sakazume, Ikeda, Harigaya, Matsubara Kawarabayashi Murakami, Nagano, Manabe, & Abe, 2002). As stated by the retrogenic models, there is an inverse and progressive pattern of functional and cognitive decline observed in Alzheimer's Disease (AD) patients compared to the developmental acquisition of the corresponding capacities in children.…”
mentioning
confidence: 99%
See 3 more Smart Citations